Retrofitting of RC Element Beam - Kalburgi, Shradha; Jadhav, Anandrao; Deshmukh, Achyut (PREPARE@u® | IEI Conferences, 2021)
Structures with the passing of time they lose their strength because of many reasons like seismic activity, soil failure due to ground motion, arises problem like damaging of roof, foundation, walls, pillars, column and beams for these structures becomes statically unsafe and solution to these problem is Retrofitting. The structure performs normally during their life span but at the end of design period of structure, the structure may not be capable of taking load. Enhancement of performance of such buildings can be done by increasing strength and strength of building can be increased by process of Retrofitting. RCC buildings undergo three different R’s name as Repair, Rehabilitation and Retrofitting. Experimental investigations on the flexural behaviour of RC beams strengthened using carbon fibre reinforced polymer (CFRP) fabrics are carried out. Externally reinforced concrete beams with epoxy-bonded CFRP sheets were tested to failure using a point load concentrated static loading system. The effect of CFRP fabric and its orientation technique on ultimate load carrying capacity and failure mode of the beams are investigated. A finite element model that is made by using ABAQUS software is used for the simulation of experiments and model gave compatible results with experiments